THE ESTABLISHMENT OF DEVELOPMENT PRIORITIES OF AIRCRAFT REPAIR ENTERPRISES IN THE FORMATION OF THE COMPETITIVENESS OF THE AVIATION MARKET IN UKRAINE - Pohorilets, Yu. (Science and Transport Progress, 2007)
Formulated basic principles and directions of creation of priorities of development of airrepairs enterprises in the system of providing of competitive airmarket in Ukraine.